Gene expression patterns of helicoverpa armigera gut proteases - Chougule, Nanasaheb P.; Giri, Ashok P.; Sainani, Mohini N.; Gupta, Vidya S. (Insect Biochemistry and Molecular Biology, 2005)
Relative quantification of reported gut proteinase cDNAs from Helicoverpa armigera larvae fed on various host plants (cotton, chickpea, pigeonpea, tomato and okra), non-host plant Pis (winged bean, bitter gourd, ground nut, and capsicum) and during larval development has been carried out using semi-quantitative RT-PCR. Five trypsin-like and three chymotrypsin-like proteinases were categorized as insensitive or sensitive to most of the proteinase inhibitors (Pis) and insensitive/sensitive to specific Pis based on their expression analysis. These results were supported by amino acid sequence analysis, where diverged amino acids were observed in the regions, which are reported to be involved in typical trypsin trypsin inhibitor interactions and critical for proteinase inhibitor resistance. Among exopeptidases (five aminopeptidase and three carboxypeptidase), HaAmi4 and HaAmi5 of aminopeptidase and HaCar1 of carboxypeptidase exhibited considerable differential expression. Elastase and cathepsin B-like proteinases were expressed at negligible levels. The proteases identified in the study would be ideal candidates for further interactions studies with protease inhibitors to understand the structural reasons of protease inhibitor insensitivity (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: expression; gut proteinases; Helicoverpa armigera; Proteinase inhibitors; RT-PCR

In vivo and in vitro effect of capsicum annum proteinase inhibitors on helicoverpa armigera gut proteinases - Tamhane, V. A.; Chougule, Nanasaheb P.; Giri, Ashok P.; Dixit, A. R.; Sainani, Mohini N.; Gupta, Vidya S. (Biochimica Et Biophysica Acta-General Subjects, 2005)
Two proteinase inhibitors (PIs), CapA1 and CapA2, were purified from Capsicum annum Linn. Var. Phule Jyoti leaves and assessed for their in vitro and in vivo activity against Helicoverpa armigera gut proteinases (HGPs). Both the inhibitors exhibited molecular weights of about 12 kDa with inhibitory activity against bovine trypsin and chymotrypsin indicating presence of probable two-inhibitor repeats of PIN II family. CapA1 and CapA2 inhibited 60-80% HGP (azocaseinolytic) activity of fourth instar larvae feeding on various host plants while 45-65% inhibition of HGP activity of various instars (II to VI) larvae reared on artificial diet. The partial purification of HGP isoforms, their characterization with synthetic inhibitors and inhibition by C. annum PIs revealed that most of the trypsin-like activity (68-91%) of HGPs was sensitive to C. annum PIs while 39-85% chymotrypsin-like activity of HGPs was insensitive to these inhibitors. The feeding of C. annum leaf extracts and two purified PIs in various doses to H. armigera larvae for two successive generations through artificial diet demonstrated their potential in inhibiting larval growth and development, delay in pupation period and dramatic reduction in fecundity and fertility. This is the first report-demonstrating efficacy of C. annum PIs against insect gut proteinases as well as larval growth and development of H. armigera. (c) 2004 Elsevier B.V. All rights reserved.
Keywords: Capsicum annum; gut proteinase; Helicoverpa armigera; insect resistance; Proteinase inhibitor

Podborer (Helicoverpa armigera Hubn.) does not show specific adaptations in gut proteinases to dietary Cicer arietinum Kunitz proteinase inhibitor - Srinivasan, A.; Chougule, Nanasaheb P.; Giri, Ashok P.; Gatehouse, J. A.; Gupta, Vidya S. (Journal of Insect Physiology, 2005)
We investigated the response of Helicoverpa armigera larvae towards ingestion of Cicer arietinum Kunitz proteinase inhibitor (CaKPI), which caused antagonistic effects on developing H. armigera larvae. CaKPI-degrading proteinases were not detectable in either control or sensitized larvae. There were negligible increases in total proteinase activity, as well as in trypsin-like and chymotrypsin-like activities of H. armigera gut proteinases (HGPs). Decrease in sensitivity of HGPs to inhibition by CaKPI was not observed when the inhibitor was fed Suggesting that the insect had not shown a specific adaptive response to dietary CaKPI. Semi-quantitative reverse transcriptase polymerase chain reaction (Q RT-PCR) analysis showed a general up-regulation of proteases in larvae that ingested CaKPI and a specific regulation of individual transcripts was not observed. CaKPI had maximum inhibitory activity against HGP derived from fourth instar larvae. CaKPI was equally potent in inhibition of HGPs derived from larvae fed on different host plants, as well as various proteinase inhibitors (Pis) to which larval adaptation was previously reported. The lack of larval response to CaKPI was attributable to the atypical active site sequence and inhibitory activity of CaKPI and/or to the pre-adaptation of H. armigera larvae due to the constant exposure to basal levels of CaKPI in chickpea seeds or a chickpea seed-based diet. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: Cicer arietinum; Helicoverpa armigera; insect response; proteinase; Proteinase inhibitor

Unraveling biochemical properties of cockroach (Periplaneta americana) proteinases with a gel X-ray film contact print method - Hivrale, Vandana K.; Chougule, Nanasaheb P.; Chhabda, Pavan J.; Giri, Ashok P.; Kachole, M. S. (Comparative Biochemistry and Physiology B-Biochemistry & Molecular Biology, 2005)
Eleven proteinase activity bands were detected in American cockroach (Periplaneta americana) gut. These were partially purified and characterized using a gel X-ray film contact print method. Cockroach gut proteinases (CGPs) show activity over a broad range of pH with maximum activity between pH 6 and 10, and optimal activity at 50-70 degrees C. CGPs were partially purified by preparative gel electrophoresis and analyzed using synthetic substrates and inhibitors. Four of the proteases exhibited chymotrypsin-like (C1 to C4) activity and seven trypsin-like (T I to T7) activity. Accuracy of the gel X-ray film contact print method is confirmed by including bovine chymotrypsin in CGP analysis. Inhibition of CGPs with different plant proteinaceous proteinase inhibitors allowed identification of potential CGP inhibitors. Our results imply that presence of several CGP activity bands, and their stability and activity over a broad pH and temperature range might contribute to adaptation of P americana to extreme environmental conditions and the polyphagous nature of the species. (c) 2005 Elsevier Inc. All rights reserved.
Keywords: activity visualization; cockroach; gut enzymes; Periplaneta americana; plant proteinase inhibitors; Proteinases

Biochemical characterisation of alpha-amylase inhibitors from achyranthes aspera and their interactions with digestive amylases of coleopteran and lepidopteran insects - Hivrale, Vandana K.; Chougule, Nanasaheb P.; Giri, Ashok P.; Chhabda, Pavan J.; Kachole, Andmanvendra S. (Journal of the Science of Food and Agriculture, 2011)
BACKGROUND: Starchy seeds are an important food and a source of dietary ingredients in many countries. However, they suffer from extensive predation by bruchids (weevils) and other pests. alpha-Amylase inhibitors are attractive candidates for the control of seed weevils, as these insects are highly dependent on starch as an energy source. RESULTS: A proteinaceous alpha-amylase inhibitor from the seeds of Achyranthes aspera was identified, purified and characterised. In electrophoretic analysis, two prominent amylase inhibitor activity bands (AI1 and AI2) were detected. The inhibitor was purified 9.99-fold with 1206.95 total amylase inhibitor units mg(-1) protein. The molecular weight of the purified inhibitor was around 6 kDa. The isolated alpha-amylase inhibitor was found to be resistant to heat and proteolysis. Feeding analysis of Callosobruchus maculatus larvae on a diet containing seed powder of A. aspera revealed that survival of the larvae was severely affected, with the highest mortality rate occurring on the fifth day of feeding. The isolated inhibitor inhibited the majority of amylase isoforms of C. maculatus, Tribolium confusum and Helicoverpa armigera in electrophoretic analysis and solution assays. CONCLUSION: The information obtained in the present investigation could be useful for a genetic engineering approach that would make seeds resistant to storage pest infestations. (C) 2011 Society of Chemical Industry
Keywords: Achyranthes aspera; Amylase inhibitors; amylases; Callosobruchus maculatus; Tribolium confusum